Estudo peptídico e determinação do perfil de metabólitos de venenos de escorpiões da família buthidae: Tityus serrulatus, Tityus bahiensis e Tityus obscurus - Dias, Nathalia Baptista [UNESP] (2016)
Numerous studies produced in the last 30 years, come elucidating structures and biological activities of various components of animal venoms, showing their complex compositions. The scorpion venoms are complex mixtures of biologically active compounds, such as low molecular weight compounds, peptides and proteins, the latter being the most widely studied. To the present time not much is known about the small peptides and metabolites of scorpion venoms, requiring research to expand this knowledge. This study aimed to obtain a detailed peptide profile of the venoms of T. serrulatus, T. bahienis and T. obscurus species, focusing primarily on small linear neglected peptides in scorpion venom. The extraction in 50% acetonitrile was one of the strategic differences for this purpose and the separation and sequencing of these peptides were performed "on-line" using an LC-ESI-ITTOF system. The peptide components of the scorpion venoms are distributed along the molar mass range of 400-4000 Da, and in this study we could detect the presence of 521 different peptides in T. serrulatus venom, 460 peptides in T. bahiensis and 517 in T. obscurus. It was also possible to establish the peptide profiles of the venoms of the three species studied, as well as to obtain the sequence of 66 peptides, some of which had similarities to known already toxins of scorpions. Thirteen of the newly detected peptides, containing between 6 and 19 amino acids, were synthesized and characterized with proposal to obtain their biological activities, such antibiosis, hemolysis, mast cell degranulation, LDH, open field test, pain and inflammation in mammals, showing some particularly activities in hemolysis, pain and mammals locomotion. This work also revealed the metabolites profile in these venoms with a LCMS-Q-TOF-MS system for qualitative and quantitative analysis. For this purpose, we standardized the chromatographic conditions with the use of ion pairing chromatography to better separation and identification of compounds such as biogenic amines, polyamines, amino acids, nucleosides derivatives, etc., detected in the venoms. The chemical complexity demonstrated in this study corroborates with the fact that small peptides and metabolites should act in synergism with large toxins in poisonings, increasing its effects on victims by these animals.